KESULITAN BELAJAR BAHASA ARAB PADA MATERI MUHASDASAH (Studi Analisis Deskriptif Terhadap Siswa Kelas VIII MTsS Pante Ceureumen Kabupaten Aceh Barat) - Muhammad Riza Riza (Koordinator Perguruan Tinggi Agama Islam (KOPERTAIS) Wilayah V Aceh, 2020)
This study examines the difficulties of learning Arabic in the content of Muhadasah faced by eighth grade students of MTsS Pante Ceureumen in West Aceh district. The underlying problem was that the students were unable to perform muhadasah activities in Arabic learning in the classroom. The purpose of this research is to identify difficulties and obstacles faced by the eighth grade students of MTsS Pante Ceureumen,West Aceh district, in learning Muhadasah and also to propose solutions that might support the eighth grade students to learn Muhadasah at school. This research employs qualitative method. The respondents in this study were 17 people. The results indicate that there are some difficulties and obstacles in the implementation of Muhadasah learning in the eighth class of MTsS Pante Ceureumen of West Aceh district. Furthermore, there are solutions that could be done to improve the students’ ability in learning Arabic, especially in mastering muhadasah in MTsS Pante Ceureumen of West Aceh district. The recommendation of this study is that all elements of the school and community should support the creation of a good and conducive language learning atmosphere.